Segmental bioimpedance and anthropometry improve machine learning prediction of grip strength in healthy young adults - Najjar, Helen; Issa, Khouloud; Badawe, Heba M.; Khraiche, Massoud L. (Frontiers in Bioengineering and Biotechnology, 2026)
ObjectiveAccurate, non-invasive assessment of muscle strength remains a key challenge for functional health monitoring and wearable systems. This study investigates whether segmental bioimpedance (BioZ) and anthropometry measurements from the wrist and forearm can predict hand grip strength (HGS) in healthy young adults, and characterizes how measurement site, frequency, and applied pressure influence BioZ signal behavior, which are critical factors for translating BioZ into wearable applications.MethodsWe recruited twenty healthy young adults who underwent standardized HGS testing alongside segmental BioZ measurements at the wrist and forearm using a bipolar electrode configuration. Anthropometric variables including age, height, body mass, and limb circumference were recorded. Nonparametric statistical analyses were used to examine anatomical site-specific differences and associations among BioZ, circumference, and HGS. Multiple linear regression (MLR) and random forest (RF) regression models were developed to estimate HGS from anthropometric and localized BioZ features and evaluated using leave-one-out cross validation. In addition, exploratory single-subject experiments were conducted to assess BioZ responses to varying frequency, applied pressure, and electrode configuration at both anatomical sites.ResultsAt the cohort level, forearm BioZ values were higher than wrist BioZ (p = 0.0001) and inversely correlated with forearm circumference (ρ = −0.54, p = 0.014). Forearm circumference showed the strongest positive association with HGS, while forearm BioZ exhibited a moderate inverse association. Incorporating localized forearm BioZ into baseline improved predictive performance (RF regression: R2cv = 0.44). A size-normalized BioZ index further enhanced prediction accuracy, achieving the highest in RF regression models (R2cv = 0.56). Frequency- and pressure-dependent analyses revealed that high-frequency BioZ increased linearly with applied pressure, whereas low-frequency BioZ exhibited non-linear and less stable behavior, suggesting sensitivity to tissue compression and local fluid redistribution.ConclusionThis pilot study demonstrates that localized, size-normalized forearm BioZ provides physiologically complementary information to basic anthropometry for estimating HGS in healthy young adults. By integrating cohort-level modeling with exploratory mechanistic experiments, the findings provide insight into the anatomical and mechanical determinants of localized BioZ behavior. This supports the potential utility of combining experimental and computational approaches to inform the future development of next-generation BioZ-based wearable systems for non-invasive assessment of muscle strength, rehabilitation progress, and early signs of muscular decline.